Study of Youth Participation in Development Based on Regional Spatial Profile: Case Study of Urban and Rural Villages in Temanggung, Indonesia - Hafzhi Nur Azmi; Holi Bina Wijaya (JAMBURA GEO EDUCATION JOURNAL, 2024)
The participation of youth is difficult to perceive, considering the numerous influencing factors, diverse challenges, and environments they face. There are many factors that influence youth participation, one of which is where they live. Previous studies describe forms of youth participation in villages and cities as dynamic, with many differences but also many similarities. The purpose of this study was to examine youth participation in urban and rural villages in Temanggung Regency in regional development. This participation is seen from youth participation in social activities, community organizations, as well as providing opinions on development activities, and what factors influence them. This research uses a quantitative approach with scoring analysis through questionnaires distributed to 40 urban and rural villages or 15% of the total villages in Temanggung Regency, cluster analysis to describe regional groups based on youth participation, and spatial overlay analysis to describe regional spatial profiles based on youth participation . The results of this research are that there is no significant difference between youth participation in urban and rural villages, as indicated by the clusters formed. Youth involvement in social activities and community organizations is relatively high, however involvement in providing opinions for development activities is still a challenge, both in urban and rural villages. The homogeneity of the population in urban and rural villages in Temanggung Regency is one indication of the reason for the absence of significant differences between youth participation in villages and urban villages. With these results, the approach to enhancing youth participation in Temanggung Regency can be carried out in a general manner, through a culturally-based approach that has been proven to attract youth participation in Temanggung Regency.